2019
DOI: 10.18671/scifor.v47n124.17
|View full text |Cite
|
Sign up to set email alerts
|

Florística e dinâmica da biomassa em dois sistemas de manejo na Floresta Ombrófila Mista

Abstract: O presente estudo teve por objetivo estimar e estratificar o estoque de biomassa em dois sistemas de manejo, sendo o primeiro um fragmento de Floresta Ombrófila Mista Secundária (FOMS) e o segundo um fragmento de Floresta Ombrófila Mista em Sistema Silvipastoril (FOMSP), correlacionado com a florística e a dinâmica da biomassa no período de 2013 e 2016, no município de Turvo, PR. Os dados foram obtidos de duas parcelas permanentes, sendo de 1,8 hectares em área com FOMSP e 1,68 hectares em área de FOMS, subdiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…Ribeiro et al, (2017) found root biomass stock values close to those found in this work in eucalyptus area, with average value close to 2.00 mg ha -1 . In another work carried out by Garcia et al (2019), the authors found in their work root biomass stock value in eucalyptus area much higher than that found in this work, 17.06 Mg ha -1 .…”
Section: Resultscontrasting
confidence: 72%
“…Ribeiro et al, (2017) found root biomass stock values close to those found in this work in eucalyptus area, with average value close to 2.00 mg ha -1 . In another work carried out by Garcia et al (2019), the authors found in their work root biomass stock value in eucalyptus area much higher than that found in this work, 17.06 Mg ha -1 .…”
Section: Resultscontrasting
confidence: 72%